Impact of type and level of stabilizers and fermentation period on the nutritional, microbiological, and sensory properties of short-set Yoghurt - Eze, C.M.; Aremu, K.O.; Alamu, Emmanuel Oladeji; Okonkwo, T.M. (Wiley, 2021)
This study aimed to produce short set yoghurt with different stabilizers at different concentrations and determine the effects of the stabilizers and length of fermentation on the nutritional, microbiological, and sensory properties of short set yoghurt. Stabilized yoghurt samples were produced using 0%, 0.5%, and 1.0% concentrations of carboxyl methylcellulose (CMC), corn starch, and gum acacia with different fermentation periods (1–5 hr), respectively. Samples were analyzed for the proximate, physicochemical, microbial, and sensory properties using standard laboratory methods. Results showed that an increase in stabilizer concentration and fermentation time decreased the moisture content but increased the total solids, protein, fat, ash, sugars, pH level, and total titratable acidity. The viscosity of the yoghurt samples significantly (p < .05) increased with the addition of stabilizers (1.48 ± 0.03 cP to 275.57 ± 4.08 cP), with CMC having the highest increase (p < .05) and gum acacia the least. However, the lactic acid production reduced as the concentration of stabilizers increased but showed an increase with fermentation time. The total viable count (TVC) reduced significantly (p < .05) with an increase in the concentration of stabilizer and fermentation time. Hence, short set yoghurt samples containing CMC yielded highest protein (0.5%), fat (1.0%), and ash contents (1.0%). Yoghurt samples produced with a 1.0% concentration of gum acacia gave an optimum pH (0.5%), TTA, mouthfeel, appearance, flavor, and taste. In contrast, yoghurt produced with corn starch produced the most desirable overall acceptability, viscosity, total solids at 1.0%, and TVC (at 0.5%) concentration.